Understanding the pull motivations of Malaysian women music teachers as music entrepreneurs - Cheong, Ku Wing (Universiti Pendidikan Sultan Idris, 2018)
Entrepreneurship generally refers to small business ownership which implies quality of innovation and initiative in creating a new venture. Previous studies on entrepreneurship have indicated that pull and push factors in motivation and the environmental influences are the two main dynamic aspects that prompt women into their decision in creating their own business. In the Malaysian context, some women music teachers have ventured into establishing music businesses after several years of contribution in music teaching. What are the pull factors and influences that prompted these women music teachers into music business ownership after some years of music teaching? This study aims to examine and explore the pull motivational and influencing factors of why women music teachers endeavour in setting up music studios, music schools and entering into small music business ownership. In-depth interviews were conducted with 3 women music entrepreneurs and data was analysed for emerging themes. The findings provided evidence for the better understanding of the pull motivational and influencing factors of the women music entrepreneurs.